2019
DOI: 10.1021/acs.joc.9b01120
|View full text |Cite
|
Sign up to set email alerts
|

4,5,5-Trimethyl-2,5-dihydrofuran-Based Electron-Withdrawing Groups for NIR-Emitting Push–Pull Dipolar Fluorophores

Abstract: In the context of molecular engineering of push–pull dipolar dyes, we introduce a structural modification of the well-known electron-accepting group 2-dicyanomethylidene-3-cyano-4,5,5-trimethyl-2,5-dihydrofuran (TCF). Introduction of a (benzo­[d]­thiazol-2-yl) moiety failed, and unexpected structures were obtained. On the other hand, phenylthio and phenylsulfonyl entities were successfully introduced at position 3 of the 2-(dicyanomethylidene)-2,5-dihydrofuran ring, giving access to new electron-acceptor group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…All dyes in this study showed strong solvatochromism due to their strong push-pull character ( Figure S4, Supporting Information for dyes IV and V; for I-III, [30] [31] [31] ). The Lippert-Mataga model was used to fit the Stokes shifts of the dyes to the solvent orientation polarizability (Δf) ( Figure S5 and Table S2, Supporting Information).…”
Section: (3 Of 11)mentioning
confidence: 97%
See 2 more Smart Citations
“…All dyes in this study showed strong solvatochromism due to their strong push-pull character ( Figure S4, Supporting Information for dyes IV and V; for I-III, [30] [31] [31] ). The Lippert-Mataga model was used to fit the Stokes shifts of the dyes to the solvent orientation polarizability (Δf) ( Figure S5 and Table S2, Supporting Information).…”
Section: (3 Of 11)mentioning
confidence: 97%
“…DPF dyes (I-III) undergo ICT though a fluorene π-bridge between diphenylamine and an acceptor group: 1,3-indandione (I), 2-(dicyanomethylene)-3-phenylthio-4,5,5-trimethyl-2,5-dihydrofuran (II) and 2-(dicyanomethylene)-3-phenylsulfonyl-4,5,5trimethyl-2,5-dihydro-furan (III). [30,31] Dye IV contains N- (2-methoxyphenyl)carbazole as the donor and the same acceptor as II. Finally, dye V contains N-ethylcarbazole as a donor and 4,5,5′-trimethyl-3-(phenylsulfonyl)furan-2(5H)-one as an acceptor.…”
Section: Optical and Electrochemical Properties Of Push-pull Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Nevertheless, elongated polymethine chains have recently attracted considerable interest because several groups could show that merocyanine dyes with extended polymethine chains (mostly consisting of three double bonds) may have better fluorescence properties compared to their homologues with shorter polymethine chains. [15][16][17] Better alignments could also be realized for elongated molecules in liquid-crystalline hosts, which is of interest for polarizers. 18 Furthermore, with longer polymethine chains, the near-infrared (NIR) spectral range can be reached, which is of interest for biomolecular imaging applications.…”
mentioning
confidence: 99%
“…Such a finding suggests that TCBDs present surprising potentialities as NIR emitters, which find various applications such as NIR-OLED 30 or biological imaging, as these wavelengths allow for improved penetration depths compared to visible-wavelength imaging. 28 Furthermore, while the development of small organic molecules as NIR-I dyes undoubtedly remains a challenging task, 31 the design of efficient fluorophores reaching the second near-infrared window (NIR-II, 1000-1700 nm) is an emerging field that may provide considerable advance in deep-tissue imaging. 29 Interestingly, considering the rather broad signal shape of compounds 1 and 2 (with a full width at half maximum of 195 nm in both cases), a significant portion of the PL bands is located in the NIR-II region: this particular PL accounts for 10% of the emission of 1, and 30% of that of 2.…”
mentioning
confidence: 99%